Challenging Western Marxism: Socialism and “New Projectment” in Today’s China (World Marxist Review, 2024)
Its growing influence on the world has made understanding China the order of the day. This article aims to tackle this research in order to overcome the common understanding that fits the Chinese experience into fixed analytical categories, seeking to configure a new rational determination in which “the concept is manifested in the real movement”. As it is an experience that takes place in the context of the anti-imperialist struggle, we admit that Chinese socialism is developing based on Marxism as a science of political power, in opposition to the postulates of so-called “Western Marxism”. We argue that without a new cognitive grammar that allows us to think about and understand the flow of the totality of opposites of historical being, social science will make little progress in producing theories, concepts and categories that correspond to a profound vision of this unique phenomenon in history. We conclude our examination of the Chinese experience based on two fundamental categories: socialism and projectment.